Sensitivity and Specificity of RIPASA Score in Diagnosis of Acute Appendicitis: A Cross-Sectional Study - Hashmi, Syed Daood; Aziz, Majid; Naeem, Muhammad; Saeed, Bilal; Mazhar Rizvi, Syed Ali; Jalil, Meezan (Pakistan Armed Forces Medical Journal, 2026)
Objective: To determine the diagnostic accuracy of RIPASA score in diagnosis of acute appendicitis with histopathology as the gold standard.Study Design: Cross-sectional study.Place and Duration of Study: Combined Military Hospital, Rawalpindi, and Pak Emirates Military Hospital, Rawalpindi, Pakistan, from Apr to Sep 2023.Methodology: A total of fifty-one patients fulfilling the inclusion criteria and diagnosed clinically to have acute appendicitis were included in the study. In all these patients, RIPASA scores were calculated. Patients then underwent appendectomy, and the removed appendix was sent for histopathological analysis. A 2x2 table was drawn for calculating SN, SP, PPV, NPV, and accuracy. Data was analyzed using SPSS v22.00.Results: Median age of our study pool was 19(14 – 29) years. Thirty-five (68.63%) patients were male, and sixteen (31.37%) were female. Median duration of symptoms was 6(2 – 9) hours. We found that the sensitivity, specificity, positive predictive value, negative predictive value, and accuracy of RIPASA score in the diagnosis of acute appendicitis was 89.74%, 83.33%, 94.59%, 71.43% and 88.24%, respectively.Conclusion: RIPASA score is highly useful in making diagnosis of acute appendicitis and should be used regularly before a decision for surgery is made.